Absence of Cultural Awareness Training in International Non-Governmental Organizations. Issue Volume 34:Issue s1(2019) (May 2019) - Hart, Alexander; Issa, Fadi
Abstract : Introduction: Cultural awareness is the understanding of differences in cultures, and openness to these differences. It is a vital step in the development of cultural sensitivity and becoming operationally effective when working within different cultures. The benefits of Cultural Awareness have become apparent in recent decades, including within governments, militaries, and corporations. Many organizations have developed Cultural Awareness training for their staff to improve cross-cultural cooperation. However, there has not been a large movement toward cultural sensitivity training among Non-Governmental Organizations (NGOs) who provide aid across a number of countries and cultures. Cultural Awareness can be a useful tool which enables an NGO to better serve the populations with which they engage. Aim: To evaluate the presence within International NGOs of Cultural Awareness Training to employees and volunteers. Methods: Ten of the largest international NGOs were identified. Their websites were evaluated for any mention of training in Cultural Awareness available to their employees and volunteers. All 10 were then contacted via their public email addresses to find out if they provide any form of Cultural Awareness training. Results: Of the ten NGOs identified, none have any publicly available Cultural Awareness training on their websites. One NGO deals with cultural awareness by only hiring local staff, who are already a part of the prevalent culture of the area. None of the others who responded have any cultural awareness training which they provide. Discussion: Cultural awareness is a vital tool when acting internationally. Large NGOs, which operate in a wide range of cultures, have an obligation to act in a culturally aware and accepting manner. Most large NGOs currently lack cultural awareness training for their employees and volunteers. It is time for these NGOs to develop, and begin to employ, cultural awareness training to better prepare their staff to serve international populations.